Characterization of the co‐elution of host cell proteins with monoclonal antibodies during protein A purification. (6th May 2016) - Zhang, Qingchun; Goetze, Andrew M.; Cui, Huanchun; Wylie, Jenna; Tillotson, Ben; Hewig, Art; Hall, Michael P.; Flynn, Gregory C.
Abstract : Protein A chromatography is commonly used as the initial step for purifying monoclonal antibody biotherapeutics expressed in mammalian tissue culture cells. The purpose of this step, as well as later chromatography steps, is, in part, to remove host cell proteins (HCPs) and other related impurities. Understanding the retention mechanism for the subset of HCPs retained during this step is of great interest to monoclonal antibody (mAb) process developers because it allows formation of a guided HCP clearance strategy. However, only limited information is available about the specific HCPs that co‐purify with mAbs at this step. In this study, a comprehensive comparison of HCP subpopulations that associated with 15 different mAbs during protein A chromatography was conducted by a 2D‐LC‐HDMS E approach. We found that a majority of CHO HCPs binding to and eluting with the mAbs were common among the mAbs studied, with only a small percentage (∼10% on average) of a mAb's total HCP content in the protein A (PrA) eluate specific for a particular antibody. The abundance of these HCPs in cell culture fluids and their ability to interact with mAbs were the two main factors determining their prevalence in protein A eluates. Potential binding segments for HCPs to associate with mAbs were also studied through their co‐purification with individual Fc and (Fab′)2 antibody fragments. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:708–717, 2016